Pharmaceutical Standardization of Amapachaka Vati: A Herbo-Mineral Formulation - Deepika Rathod; Kruti Vyas (International Journal of Ayurveda and Pharma Research, 2025)
Introduction: Standardization of formulation is essential to certify their quality, purity and reproducibility. The standard of an Ayurvedic product can be assessed by analysing the analytical parameters of raw drugs, in-process materials, and the finished products. Amapachaka Vati is a well-known Ayurvedic herbo-mineral formulation which is mentioned by Chikitsapradip in Agnimandhya and Ajirna. Till date, no work has been done on pharmaceutical standardization of Amapachaka Vati. The present study was aimed to develop Standard Manufacturing Procedure (S.M.P.) of Amapachaka Vati. Materials and methods: In pharmaceutical process, 3 batches of Amapachaka Vati were carried out with the Shodhana procedure of required ingredients. Organoleptic and physicochemical analysis of raw, in-process and finished product were done. HPTLC and heavy metal analysis of finished product were also carried out. Results: In all three batches of Amapachaka Vati average 97.11% yield was found. Prepared Vati was greenish brown in color with characteristic odor. Physical parameters of Vati were in compliance with the general consideration of IP standards. HPTLC profile shows 6,5,8 peaks in 254, 366, and 540 nm. Conclusion: The preparation method of Amapachaka Vati carried out here can be considered as Standard Manufacturing Procedure (S.M.P.) as no previous standards are available for this preparation. Evaluated parameters for Amapachaka Vati can be used in future reference as a standard.